Pengembangan Soal Faktual, Konseptual, dan Prosedural Pada Materi Tekanan Zat Kelas VIII SMP/MTs - Fitria, Jazunika; Wijayadi, Andri Wahyu (Journal of Science and Education Research, 2023)
Core knowledge competencies require students to master the dimensions of factual, conceptual, and procedural knowledge. If the knowledge gained by students is not balanced, it will affect their way of thinking. Knowledge competence can be measured one way through the problem instrument. Facts on the ground state that the instrument questions used have not been able to measure these three pieces of knowledge. The purpose of this study is to describe the development process and products resulting from the development of factual, contextual, and procedural questions on material stress. This research is development research that uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results obtained are in the form of 10 questions, which consist of 7 multiple choice and 3 essays. Based on theoretical validation by the validator, it was declared very valid with an average score of 97.03%. The reliable value of multiple-choice questions is 0.726 and essay questions are 0.826 with high criteria. The difficulty level of multiple-choice questions and essays is 90% with moderate criteria. The different power of multiple-choice questions is 50% with good and sufficient criteria.